Factores de riesgo asociados a infecciones de sitio quirúrgico en pacientes post cesareadas, en el Hospital Regional de Loreto de Julio del 2018 a Julio del 2019 - Jarama Paredes, Manuel Eduardo (2024)
The great requirement to save lives has always been a priority in medicine, even more so when it involves two lives joined through a complexity of nature that occurs in human pregnancy. The doctors whose hands are dedicated to saving lives were never oblivious to this outcome and, for more than 2000 years, they have made many attempts, just “attempts” to find a way out to help a happy term of pregnancy. Women always faced this situation and together with midwives suffered in many remote places the decline of their fight against such helplessness over the years. Surgery tried to glimpse this happy encounter for 200 years, but many situations became complicated due to the lack of development of different professions associated with medicine. It has been almost 50 years since the operations have been a total success. Although the advancement of surgical techniques focused on the infectious preventive part, anesthetic specialization and surgical room protocols is not achieved in 100 percent of cases, today we can say to society “mission accomplished, They saved 2 lives”. Complications from surgical wounds are nothing more than a small stone here, and we will only emphasize them so as not to fall into it. Thanks to the surgical team and everyone who is dedicated to surgery.